Crème de la Créature: Dietary Influences on Behavior in Animal Models - Sarangi, Manaswini; Dus, Monica (Frontiers in Behavioral Neuroscience, 2021)
In humans, alterations in cognitive, motivated, and affective behaviors have been described with consumption of processed diets high in refined sugars and saturated fats and with high body mass index, but the causes, mechanisms, and consequences of these changes remain poorly understood. Animal models have provided an opportunity to answer these questions and illuminate the ways in which diet composition, especially high levels of added sugar and saturated fats, contribute to brain physiology, plasticity, and behavior. Here we review findings from invertebrate (flies) and vertebrate models (rodents, zebrafish) that implicate these diets with changes in multiple behaviors, including eating, learning and memory, and motivation, and discuss limitations, open questions, and future opportunities.